Heavy metals and genetic variations in folate metabolism pathway: A gene-environment interaction - Amandeep Kaur; Mohan Jairath; Anupam Kaur (Wolters Kluwer Medknow Publications, 2023)
Heavy metals are capable of inducing toxicity even at lower levels and the contamination adversely impact humans, animals, and plants thus, resulting in variety of health issues. Thus, the present study investigated the presence of metals in the serum of mothers (n = 77) having Down syndrome children and healthy control mothers (n = 86) and the possible association of heavy metals with genotype. We found that increased levels of cobalt were significantly associated with MTHFR 677 C>T, RFC 80 A>G, and CBS844ins68 polymorphisms in cases. Increased levels of potassium showed a significant association with MTHFR 1298 A>C and RFC 80 A>G Single Nucleotide Polymorphism (SNP). Arsenic had association with MTHFR 677 C>T, RFC 80 A>G, and CBS844ins68 and lead showed an association with MTHFR 1298 A>C SNP. An association between heavy metals and SNPs in the genes leads to the reproductive outcomes in a significant manner.